(untitled) (Linguamática, 2014)
In this paper we investigate the applicability of Barzilay and Lapata’s (2008) entity-grid model in the evaluation of local coherence in scientific abstracts written in Portuguese. More specifically, we focused on assessing whether such model could be employed in the implementation of a classifier capable of detecting linearity breaks that affect text coherence. Our experimental results are close to those of the original entity-grid model for English and very similar to the results reported by related works for other languages. In experiments with scientific abstracts, results are close to those obtained by human judges, showing that the entity-grid model can be used in the investigated context.